Influence of dispersed β phase on local deformation pattern in mill-annealed Ti-Fe-O alloy under dwell fatigue loading. (November 2021) - Yin, Liangwei; Umezawa, Osamu
Highlights: Load-displacement curves of β single crystal show reasonable agreement between nanoindentation tests and dislocation mechanism-based crystal plasticity modeling. Intergranular β lath within the rogue grain combination reduces the dwell fatigue sensitivity of titanium alloys with globular structure. Geometrical compatibility of the α / β interface significantly affects the stress redistribution phenomenon. Increased peak stress in the intergranular β lath may cause competing dwell fatigue failure modes at the high stress state. Abstract: Grain-scale dwell fatigue behavior in Ti-Fe-O alloy is elucidated, with attention focused on the stress redistribution phenomenon that occurs within the soft-hard grain combination. Elastoplastic properties of the β phase are determined using nanoindentation and crystal plasticity modeling. On this basis, the role of intergranular β lath on stress redistribution is evaluated. Redistribution of stress from the soft to hard α grain is inhibited in the presence of intergranular β lath during dwell period. Meanwhile, the peak stress in the β lath is enhanced. This may result in the competition of two dwell fatigue failure modes at high stress state.